V.1 - "Guthrie, W.K.C." (Cambridge, 1962)
This volume marks the beginning of an enterprise undertaken on the initiative of the Syndics of the Cambridge University Press. They decided Greek philosophy in English, on a considerable scale. The only such history available is the four volume translation of Theodor Gomperz's Greek Thinkers, the last volume of which was finished by Gomperz in 1909.
Keywords: Philosophy